Correction to: Exploring Super-Resolution Spatial Downscaling of Several Meteorological Variables and Potential Applications for Photovoltaic Power (Scientific Reports, 2024 14 1 7254 10.1038/S41598-024-57759-8) - Cordero-Carrasco, R; Christin-Feron, S (Nature Research, 2024)
Correction to: Scientific Reportshttps://doi.org/10.1038/s41598-024-57759-8, published online 27 March 2024 The original version of this Article contained an error in the legend of Figure 7. “MRI time series differences for temperature (°C) as shown in Fig. 6a, except for winter (DJF) and summer (JJA) months, which are shown in (a) and (b), respectively. Mount Fuji’s location corresponds to the high (low) patch in the southwest in panel a (b). Plots were generated using Python’s Matplotlib library, version 3.4.3, https://matplotlib.org/3.4.3/contents.html.” now reads: “MRI time series differences for temperature (°C) as shown in Fig. 6a, except for winter (DJF) months. Mount Fuji’s location corresponds to the high patch in the southwest. Plots were generated using Python’s Matplotlib library, version 3.4.3, https://matplotlib.org/3.4.3/contents.html.” The original Article has been corrected. © The Author(s) 2024.